2019
DOI: 10.1155/2019/4181502
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Management of a Voluminous Left Atrial Myxoma Resection in a 19 Weeks Pregnant with Atypical Clinical Presentation

Abstract: We report the case of a semi-urgent cardiac surgery, in a 19 gestation age pregnant. Despite the fact that the patient was asymptomatic, except for some palpitations, a large left auricle (LA) myxoma was fortuitously diagnosed with transthoracic echocardiography (TEE). Considering the important embolic risk, the tumor was successfully removed during cardiac surgery under cardiopulmonary bypass (CPB). Fetal bradycardia following defibrillation under stable maternal and CPB conditions was successfully managed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Consequently, the dose of NMBA should be reduced ( 24 ). In a case of left atrial myxoma resection reported by Alexis et al ( 26 ), a low dose of nicardipine, a calcium channel blocker, was used to inhibit uterine contractility and may show an advantage to restore FHR.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the dose of NMBA should be reduced ( 24 ). In a case of left atrial myxoma resection reported by Alexis et al ( 26 ), a low dose of nicardipine, a calcium channel blocker, was used to inhibit uterine contractility and may show an advantage to restore FHR.…”
Section: Discussionmentioning
confidence: 99%